1999
DOI: 10.1093/intimm/11.12.1999
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine phosphatase SHP-1 influences thymocyte selection by setting TCR signaling thresholds

Abstract: Modulation of the strength of signals from the TCR determines the outcome of positive and negative selection in thymocyte development. Previous studies have demonstrated that SHP-1 plays a role in determining signal strength from the TCR. Here, we have taken a genetic approach to test whether SHP-1 plays a role in T cell selection in the thymus. Experiments in which a dominant negative mutant of SHP-1 was expressed in the BYDP hybridoma cell line confirmed that SHP-1 regulated TCR signaling in a cell-autonomou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 49 publications
6
87
1
Order By: Relevance
“…We had previously reported that SHP-1 plays a role during thymic T cell development by influencing the TCR signal strength (30). Using a transgenic TCR system, bred into the motheaten background, we observed that SHP-1 is involved in setting the thresholds for positive and negative selection (31). Other reports have also noted similar effects of SHP-1 on thymic selection (32)(33)(34).…”
Section: Deficiency Of the Src Homology Region 2 Domain-containing Phsupporting
confidence: 55%
See 4 more Smart Citations
“…We had previously reported that SHP-1 plays a role during thymic T cell development by influencing the TCR signal strength (30). Using a transgenic TCR system, bred into the motheaten background, we observed that SHP-1 is involved in setting the thresholds for positive and negative selection (31). Other reports have also noted similar effects of SHP-1 on thymic selection (32)(33)(34).…”
Section: Deficiency Of the Src Homology Region 2 Domain-containing Phsupporting
confidence: 55%
“…(BALB/c:me/ϩ), (BALB/c:ϩ/ϩ:DO11.10 TCR-Tg ϩ ), and (BALB/c:me/ ϩ:DO11.10 TCR-Tg ϩ ) mice (31) were bred in our colony to generate the various genotypes. Genotyping for all mice was performed as described (31).…”
Section: Micementioning
confidence: 99%
See 3 more Smart Citations